Simulated Analysis and Review of Ocean Wave Power Generators - Hajjaj, Sami Salama Hussen; Nazri, Ahmad Faizuddin Bin Ahmad (International Journal of Engineering and Technology, 2018)
With the exponential rise in human population, the need for energy is becoming a real challenge to many countries around the world. Shortages in fossil sources of energy and its rising prices are beginning to cause many socio-economic problems and unrest in many parts of the world. This brings the need and importance of finding alternative and reliable sources of power. In recent years, the power of ocean waves began to attract attention. In this article, a design of the Wave Power Generator device is presented. This design is introduced to improve the efficiency. The proposed design is compared with an existing device that exploits the sea waves, converting the its energy to electrical power. This study aims to show that the instrument would achieve a higher efficiency by generating a greater total of electricity with the appropriate design and focus. The study is simulated using MATLAB. Results of the study show the electricity energy generated improved up to 80% in contrast to the present instrument. The results of this work could lead the way towards more active implementations of wave power generators and the use of sustainable energy resources.